Prevalence of positive tuberculin skin test and associated factors among Makerere medical students, Kampala, Uganda - Kenyi Lou, Joseph; Okot-Nwang, Martin; Katamba, Achilles (African Health Sciences, 2015)
Tuberculosis infection among medical students is thought to be higher than that among comparable groups. Objectives: To determine the prevalence of positive Tuberculin Skin Test (TST) and associated factors among medical students at Makerere University. Methods: A-cross-sectional study among randomly selected medical students. Using intra-dermal technique, TST was performed by administering 0.1ml of purified protein derivative. Readings performed after 72 hours and positive TST based on an induration of ≥10mm. Results: Of 302 students selected to participate, 292 received TST and 288 were analyzed. Of 288 students, 173(60%) were pre-clinical (years 1-3) and 115(40%) clinical (years 4&5). Overall 130 students [45.1%(C.I.39.3–51.1)] had positive TST, not different from one derived from mixture analysis [46.3%(95% Bayesian credibility interval 36.5%-55.8%)]. Positive TST prevalence among pre-clinical was 39.9%(67/173) compared to 53.0%(61/115) among clinical students, OR=1.70,C.I.(1.06-2.74) and increases in a linear pattern with increasing years of study (p=0.002,OR=5.04). Conclusion: The prevalence of TB infection among medical students was twice higher than that of adults living in the suburbs and higher among those in clinical relative to pre-clinical years suggesting that exposure and infection might be related to clinical work. We recommend urgent institution of infection control measures.
Keywords: Tuberculin skin testing; Tuberculosis; Medical students